Network ties and survival: A study of small commercial poultry farms in Ghana. (February 2017) - Acheampong, George; Narteh, Bedman; Rand, John
Poultry farming has been touted as one of the major ways by which poverty can be reduced in low-income economies like Ghana. Yet, anecdotally there is a high failure rate among these poultry farms. This current study seeks to understand the relationship between network ties and survival chances of small commercial poultry farms (SCPFs). We utilize data from a 2-year network survey of SCPFs in rural Ghana. The survival of these poultry farms are modelled using a lagged probit model of farms that persisted from 2014 into 2015. We find that network ties are important to the survival chances of the SCPFs in Ghana. Distribution ties are associated with negative survival chances and this is not even reversed if the human capital of the owner increases although managers with higher human capital and higher distribution ties experience positive effects. Industry ties are associated with positive ties but this probability reduces as the number of industry ties increases but moderation with dynamic capability of the firm reverses this trend. Our findings show that not all network ties aid survival and therefore small commercial poultry farmers need to be circumspect in the network ties they cultivate and develop.